The karate mouse - Ferrario, Giuseppe; Brusco, Federico; Grassini, Valentina, 1981-; Sacchi, Chiara (New York : Scholastic, 2005)
Geronimo Stilton gets caught up in the World Karate Championships, thanks to the efforts of Bruce Hyena and Piccolo Tao, Bruce's super-sporty cousin. Geronimo only has a week to become real champion material! Will Geronimo manage to overcome his fears in order to win the competition?
"English translation ... by Atlantyca S.p.A."--T.p. verso.
"#40"--Spine.
G2
Keywords: Stilton, Geronimo (Fictitious character) -- Juvenile fiction; Mice -- Juvenile fiction; Karate -- Juvenile fiction; Detective and mystery stories; Karate -- Fiction; Mice -- Fiction; Journalists -- Fiction; Mystery and detective stories